1999
DOI: 10.1007/pl00013862
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Size-Related Variations in Current-Year Shoot Structure in Eight Deciduous Tree Species

Abstract: The relationships between stem length (SL) and leaf display index (LDk the ratio of leaf area to stem length) of current-year shoots are compared for eight deciduous tree species. Two patterns were found in the relationships. In seven species (Amono, Aesculus furbinata, Betula gmsa, Catphs tdnnwskih Fwus emnab, Rerocarya rhoifolia, and Quercus mongolica var.grosseserrata), LDI decreased exponentially with SL, which suggests that short current-year shoots favor leaf-display over space-acquisition, and the rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 21 publications
5
46
0
2
Order By: Relevance
“…Accordingly, J. curcas adapt to low light availability by growing toward the light to maintain photosynthesis. The higher leaf display index and leaf area ratio in January 2011 in shade-grown J. curcas indicated resource allocation for optimizing light interception (Yagi & Kikuzawa 1999;Yagi 2000). Matos et al (2009) showed that J. curcas grown in shade had higher leaf area and leaf chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, J. curcas adapt to low light availability by growing toward the light to maintain photosynthesis. The higher leaf display index and leaf area ratio in January 2011 in shade-grown J. curcas indicated resource allocation for optimizing light interception (Yagi & Kikuzawa 1999;Yagi 2000). Matos et al (2009) showed that J. curcas grown in shade had higher leaf area and leaf chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
“…These morphological indices show the distribution of foliage in the plant crown and the optimization of biomass allocation among stems, roots, and leaves (Yagi & Kikuzawa 1999;Yagi 2000;Souza et al 2009). The distribution of foliage also indicates how the plant uses available resources and adjusts to stresses such as drought and shade.…”
Section: Shoot-foliage Relationshipsmentioning
confidence: 99%
“…On the one hand, since only thick twigs can physically and physiologically support large leaf area and mass, stem diameter of a twig (but not stem length) is positively correlated with both individual leaf size and total leaf area supported by the twig (White 1983a(White , 1983bAckerly and Donoghue 1998;Brouat et al 1998;Preston and Ackerly 2003;Westoby and Wright 2003;Sun et al 2006;Yang et al 2009). Previous studies have shown that leaf number per unit stem length decreases with increasing stem length of currentyear shoots, both intraspecifically and interspecifically (Yagi and Kikuzawa 1999;Yagi 2000), and that leaf number per unit twig mass decreases with increasing twig size . Thus, considering the positive correlation between stem length and stem diameter in whole plants, we can expect that stem diameter and stem length would be pos-itively correlated with leaf size but negatively associated with leaf number per stem mass or length across species within twigs.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of biomass allocations to shoots and leaves followed the methodologies described by Yagi & Kikuzawa (1999), Yagi (2000), and Souza et al (2009b) and were used to identify patterns of biomass allocation and resource optimization within the crowns of species with contrasting leaf phenologies.…”
Section: Shoot-foliage Relationshipsmentioning
confidence: 99%